Behavioural economics and customer complaints in the communications sector - Xavier, Patrick; Kallinikios, J. (Communication Economics and Electronic Markets Research Centre, 2011)
The cognitive decision-making processes examined by behavioural economics help explain why consumer behaviour can deviate from that predicted by conventional economic theory. This paper indicates how a better understanding of these decision-making processes can assist in better-targeted regulatory intervention - or industry generated solutions - to empower consumers and create the conditions for more efficient market participation.Efficient market participation not only benefits consumers – in terms of choosing products, services and plans that meet their needs – but is essential to the development of effective competition. Informed empowered customers willing and able to switch from one service provider to another is necessary to exert the sustained pressure on service providers that delivers the promised benefits of competition by way of lower prices, more choice, better quality of service, technology embedment etc. Informed consumers making better decisions will also benefit industry in terms of reduced consumer complaints, reduced incidence of unpaid bills and a reduction in costs associated with handling consumer complaints arising from sub-optimal market participation based on poor information and information processing.1The ability and willingness of consumers to switch from one service provider to another is crucial since it is by switching that consumers can punish poor performance. If they were able to switch between service providers easily and at low costs, providers would need to cater to customer requirements or risk losing them to the competition. If search and switching costs are high, consumers are deterred from switching. The paper considers how behavioural economic analysis can be used to provide an additional unique perspective on consumer complaints data, helping to identify areas that require targeted policy and regulatory intervention.